Investigation of The Impacts of Social Capital on Organizational Entrepreneurship in Tehran Municipality - Kazem, Mohammad; Gharibi, Mojtaba; Rezazadeh, Seyyed Mohammad; Mosammam, Hassan Mohammadian (Makara Human Behavior Studies in Asia, 2021)
Entrepreneurship is the symbol of endeavor and success in business, and entrepreneurs play a crucial role in economic and social development of communities. Since Organizational Entrepreneurship (OE) contribute to earning stable finance required for administration of urban affairs, it is very important in the case of municipalities. For this reason, this study aims to investigate the role of social capital (SC) in the development of entrepreneurship in Tehran municipality. Research method was descriptive and non-experimental, and required data were collected through 204 questionnaires distributed among managers and experts of the organization. Stratified sampling was used, in which 37 managers and 167 experts participated. Number of male participants was 147, and number of female participants was 57. The mean age of participants was 41 years, and its standard deviation was 0.765. In order to test the research hypothesis, structural equation modeling (SEM) was used. The results of the study showed that social capital and its three dimensions (Cognitive, Relational and Structural dimensions) had positive significant effect on organizational entrepreneurship.